Synthesis and morphological study of graphenated carbon nanotube aerogel from grapeseed oil - Abdullah, Hayder Baqer; Ramli, Irmawati; Ismail, Ismayadi; Zaidi, Muhammad Azizan; Abdullah, Ahmad Aimanuddin Amzar (Springer Netherlands, 2021)
Grapeseed oil as a new source of graphenated carbon nanotube (g-CNTs) hybrids was described in this paper. Mesoporous three-dimensional (3D) g-CNT aerogel was synthesized by a floating catalyst chemical vapor deposition (FCCVD) method. The effect of the H2 gas ratio was evaluated, and the graphenated g-CNTs morphology was identified by various physico-chemical techniques, such as field-emission scanning microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), Raman spectroscopy, thermogravimetric analysis (TGA), and N2 sorption studies. Furthermore, the multi-wall carbon nanotube (MWCNT) bundles in the network were highly disordered and rounded by graphene foliate structures in which a large number of sharp edges of graphene sheets were found.